2019
DOI: 10.1111/bjhp.12357
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to medication in adults with Cystic Fibrosis: An investigation using objective adherence data and the Theoretical Domains Framework

Abstract: Objectives Adherence to nebulizer treatment in adults with Cystic Fibrosis ( CF ) is poor, and interventions are needed. This research aimed to identify the factors affecting nebulizer adherence using the Theoretical Domains Framework (TDF) and to compare these for participants with different levels of adherence. Design Data‐prompted interviews using the TDF. Methods Eighteen semi‐structured interviews were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…This was highlighted by Sawicki, Heller, Demars and Robinson [20], who interviewed 20 pairs of CF youth patients (aged 16-21 years old) with their parents and found that patients thought their treatment "makes no difference" to how they felt, which affected their intentions to adhere. These findings have been supported by the work of Arden et al [21], who found that some participants have "dysfunctional beliefs" in terms of believing that adhering to their nebuliser treatment has no impact upon their health. It was also found that some patients reported adhering to treatment when they experienced more symptoms [21], which could suggest a relationship between symptoms experienced and adherence to nebuliser treatments.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…This was highlighted by Sawicki, Heller, Demars and Robinson [20], who interviewed 20 pairs of CF youth patients (aged 16-21 years old) with their parents and found that patients thought their treatment "makes no difference" to how they felt, which affected their intentions to adhere. These findings have been supported by the work of Arden et al [21], who found that some participants have "dysfunctional beliefs" in terms of believing that adhering to their nebuliser treatment has no impact upon their health. It was also found that some patients reported adhering to treatment when they experienced more symptoms [21], which could suggest a relationship between symptoms experienced and adherence to nebuliser treatments.…”
Section: Introductionsupporting
confidence: 53%
“…These findings have been supported by the work of Arden et al [21], who found that some participants have "dysfunctional beliefs" in terms of believing that adhering to their nebuliser treatment has no impact upon their health. It was also found that some patients reported adhering to treatment when they experienced more symptoms [21], which could suggest a relationship between symptoms experienced and adherence to nebuliser treatments.…”
Section: Introductionsupporting
confidence: 53%
“…ACtiF is a 5-year program to develop and evaluate a theory-based complex intervention to improve nebulizer adherence in adults with CF. The qualitative interview study reported in this article was undertaken at the beginning of the ACtiF program, as the first step in developing an intervention to improve nebulizer adherence, by understanding the barriers and facilitators to nebulizer adherence in adults with CF (Arden et al, 2019). For more information about the intervention and pilot feasibility study, also see the work by Hind et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…However, two smaller studies in adult patients have started to question the role of forgetting in adherence behavior, suggesting that nebulizer treatments in adults may be so routinized that forgetting is not an issue (Hogan et al, 2015). In a study of the differences in barriers and facilitators to adherence of nebulizer treatments between high and low adherers, Arden et al (2019) found that forgetting was given as a reason for nonadherence by adults regardless of whether they had high or low adherence, suggesting that addressing forgetting may not be a useful way to improve adherence.…”
Section: Adherence To Nebulizer Treatments In Cfmentioning
confidence: 99%
“…This can lead to difficulties with adherence to treatment, which is very understandable. 63,125 Indeed, it would be unusual for any individual to never miss any of the treatments. Maximizing adherence requires an honest and open relationship with the individual and flexibility from health care practitioners to understand what an individual can do and to help them prioritize their treatment program.…”
Section: Treatment Burden and Adherencementioning
confidence: 99%